Pelatihan Aplikasi Pengolah Kata Pada Siswa PKL Di LKP Arvi Com - Maha Putra, Guntur; Rizaldi, Rizaldi; Zikra Syah, Arridha (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Word processing training is really needed by LKP Arvi Com students in understanding Microsoft Office. Students already have basic knowledge about word processing, but there are still many features in the software that they don't know and use in learning at LKP Arvi Com, especially at Mircosoft Office. . The main aim of this service is to improve students' computer skills and work abilities during their PKL period. This training focuses on mastering the basics of Microsoft Office (Word), which is one of the word processing applications commonly used in various work environments. In this service program, PKL students will be given intensive training on various aspects of using Microsoft Office, such as introducing the interface, arranging pages, creating tables, inserting images, using collaboration features, preparing official documents, using styles and templates. By participating in this training, PKL students at LKP Arvi Com will gain improved skills that can increase their added value in the world of work. Apart from that, this community service will also provide positive benefits for LKP Arvi Com by increasing its reputation and contribution to education and training in the local community.            Keywords: microsoft office; PKL; data processing.